Crowd Wisdom and Key Indicators in Economic Forecasting - Phillips, Peter C B (Institutional Knowledge at Singapore Management University, 2014)
Modern market economies make extensive use of economic and financial forecasts at all levels, from guiding government policy and business decisions to the choices made by individual consumers, savers and investors. Forecasting is a particularly valuable tool for governments and monetary authorities as they formulate policies and strategies for the future. Professor Peter Phillips is Sterling Professor of Economics at Yale University and Distinguished Term Professor of Economics, Keppel Professor of Financial Economics at the Singapore Management University. His research covers many areas of econometrics, its empirical applications, and its wider implementations in fields such as communications and environmental science. His latest empirical work includes an econometric analysis of the recent financial and sovereign debt crises, which has led to the development of a new warning alert system for financial market exuberance. Professor Phillips believes that crowd wisdom has a big part to play in economic forecasting, that is, the collective opinion of groups of individuals may be more accurate than the best informed individual or a single economic forecasting model. In this podcast, he shares his insights about crowd wisdom and discusses other key indicators that may point to economic instability in the future.